ESP course design for Entrepreneurship and Start-up Project Students The Case of Entrepreneurship students and Start-Up Project Holders at Souk-Ahras University - GOUBAI Nouhed (My University, 2024)
Abstract As the growing interest in English became prominent in the latest era, its importance rose high and it became a necessity to acquire the language properly. And with the surge of Entrepreneurial Projects supported by the state, it became evident that the success of young Entrepreneurs and Start-up owners within the global scene is dependent on their English proficiency. This dissertation aims to develop an English for Specific Purposes (ESP) course design tailored to the language needs of Entrepreneurship and Start-up project students through a mixed method, quantitative and qualitative. The study took place in the Entrepreneurship Centre of the University of Souk Ahras, where a questionnaire was distributed amongst the project holders and both the directors were interviewed. The findings highlighted the importance of English language proficiency in entrepreneurship education and practice, as well as the potential role of tailored ESP courses in addressing the specific language needs of students in this domain. The proposed course design incorporates language aspects, tasks, and materials aligned with the entrepreneurial context, equipping learners with the necessary communication skills for successful ventures. This study contributes to the field of ESP course design and provides a practical framework for enhancing language education in the entrepreneurship and start-up sectors. ---------------------- الملخص نظرًا للاهتمام المتزايد الذي أولته الجزائر للغة الإنجليزية كلغة أجنبية أولى بدلاً من اللغة الفرنسية، بالإضافة إلى زيادة المشاريع الريادية المدعومة من الدولة، أصبح من المهم جدًا تعلم اللغة بحيث يمكن للشباب الرياديين أن يكون لديهم فرصة للنجاح على الساحة الدولية. تهدف هذه الدراسة إلى تطوير دورة في اللغة الإنجليزية لأغراض محددة (ESP) تلبي الاحتياجات اللغوية لأصحاب المشاريع الريادية والشركات الناشئة في مركز ريادة الأعمال بجامعة سوق أهراس، باستخدام منهجية مختلطة، كمية ونوعية. تم توزيع استبيان على أصحاب المشاريع وتم إجراء مقابلة مع المديرين الاثنين للمراكز. أظهرت نتائج الدراسة أهمية تعلم اللغة الإنجليزية فيما يتعلق بمجال ريادة الأعمال. تتضمن الدورة المقترحة الجانب اللغوي، والتمارين، والمواد التي تتماشى مع السياق الريادي، مما يزود المتعلمين بمهارات التواصل اللازمة للشركات الناجحة. تساهم هذه الدراسة في مجال تصميم دورات اللغة الإنجليزية لأغراض محددة (ESP) وتقدم إطارًا عمليًا لتحسين تعليم اللغات المدمجة في قطاعات ريادة الأعمال -------------------- Résumé L’intérêt croissant qu’a donné l’Algérie a la langue Anglaise comme étant la première langue étrangère en remplacement de la langue Française, en plus de l’augmentation des projets entrepreneurials soutenus par l’état, il est devenu très important d’apprendre la langue afin que les jeunes promoteurs puissent avoir une chance de réussir sur la scène internationale. Cette recherche vise à développer un cours d'anglais pour objectifs spécifiques (ESP) adapté aux besoins linguistiques des propriétaires de projets entrepreneurials et de start-up au niveau du Centre d’Entrepreneuriat auprès de l’Université de Souk Ahras, en utilisant une méthode mixte, quantitative et qualitative. Un questionnaire a été distribué aux propriétaires des projets et une interview a été effectuée avec les deux directeurs des centres. Les résultats de la recherche ont mis en évidence l’importance d’apprendre la langue Anglaise en ce qui concerne le domaine de l’entreprenariat. Le cours proposé inclus l’aspect linguistique, les exercices, et les matériels correspondant au contexte entrepreneurial, en équipant les apprentis avec les compétences de communication nécessaires pour des entreprises réussies. Cette étude contribue au domaine de la conception des cours d’Anglais pour objectifs spécifiques (ESP) et fournit un cadre pratique pour améliorer l’enseignement des langues intégrées dans les secteurs d’entreprenariat